Karakter Morfofisiologi dan Fisikokimia Beras dengan Berbagai Dosis Pemupukan Organik dan Hayati pada Budidaya Padi Organik - Tustiyani, Isna; ,, Sugiyanta; Melati, Maya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTThe awareness of the negative impacts of conventional agriculture has been encouraging people to switch from conventional farming to the organic farming, using organic and biological fertilizers. This farming system changes will influence the character of the plant and the yield. The objective of the research was to investigate the morphophysiology and physicochemical characters of rice with various rates of organic and biological  fertilizer. The experiment was conducted at rice field in Karawang and Bogor, West Java, from May to September 2012. The experiment used a single factor randomized block design consisted of three replications with 12 treatments. The first 6 treatments were 0, 2, 4, 6, 8, 10 ton organic fertilizer ha-1, and the other 6 treatments were 0, 2, 4, 6, 8, 10 ton organic fertilizer ha-1 combined with 2 l biological fertilizer ha-1. As control treatment was application of anorganic fertilizer with the rate of 400 kg NPK (30-6-8) ha-1. Plot size was 15 m x 10 m, with a double row spacing (legowo 2:1) (25 cm x 15 cm x 50). The results showed that organic fertilizer either without or with biological fertilizers increased the weight of 1,000 grains and decreased amylose content of rice. The score of leaf color in plants with inorganic fertilizer was higher than those with organic fertilizer.Keywords: amylose, gelatinization temperature, leaf color, water uptake ratio, 1,000 grain weight